TRANSLATIONAL CELLULAR IMMUNOTHERAPY FOR CADAVERIC KIDNEY ALLOGRAFT IN UROLOGICAL PATIENTS - V. A. Fedulkina; A. V. Vatazin; A. V. Kildyushevskiy; E. S. Stolyarevich; R. O. Kantaria; A. B. Zulkarnayev (Alʹmanah Kliničeskoj Mediciny, 2016)
The first domestic experience of translational cellular immunotherapy application in recipients of cadaveric renal allograft is presented. We present the analysis of the clinical, laboratory and immunological data and also the results of transplant protocol biopsy on the 30th and 180th days after transplantation. Clinical, laboratory, immunological, and histological benefits in patients of the main group were revealed. As а result, some mechanisms that explain the possibility to form immunological tolerance were established.